Psychometric properties of the SE-Revised: A rasch model analysis - Siti Juniawati Rosa; Ahyani Radhiani Fitri; Ivan Muhammad Agung (HUMANITAS: Indonesian Psychological Journal, 2019)
Satz Ergaenzung (SE) is the first subtest in the Intelligenz Struktur Test (IST) that measures reasoning ability. Previous studies found that SE has suboptimum performance in measuring subject's ability. Therefore, this study intended to revise the SE items that were found to have poor psychometric properties, either by changing the questions and answer choices, the answer choices only, or changing the order of the questions. This study used the rasch model to determine the psychometric property of SE-revised. A total of 159 undergraduate students of a university in Riau participated in this study. The results showed that the revised SE had fulfilled the pre-requisites of unidimensionality. The instrument reliability increased after being revised, where the items of SE-revised correctly measure respondents' abilities. The revised version may be used as an improvement of the original SE, with better psychometric properties. However, there were four items with low difficulty index and two items that have DIF. Even though SE-revised is better than the original SE, further research is needed to revise the six items of SE-revised subtest.